The Origins of American Literature Studies : An Institutional History - Renker, Elizabeth (Cambridge University Press, 2013)
College and university archivists around the nation generously shared with me their knowledge about the primary materials in their care. I am particularly grateful to Patricia Albright of Mount Holyoke College; Jacqueline Brown of the Wilberforce University Archives; Bertha Ihnat of The Ohio State University Archives; Gary Lundell of The University of Washington Archives; Margery Sly of the Smith College Archives; James Stimpert of The Ferdinand Hamburger, Jr. Archives of The Johns Hopkins University; and Clifford L. Muse, Jr. of The Moorland-Spingarn Research Center at Howard University.